Systematics of the weevil genus Mecinus Germar, 1821 (Coleoptera: Curculionidae). I. Taxonomic treatment of the species - Caldara, Roberto; Fogato, Valter (Zootaxa, 2013)
Palaearctic species of the weevil genus Mecinus Germar, 1821 are revised. A total of 47 species are recognized, one of which, M. baridioides sp. n. is new to science. Mecinus dorsalis var. tavaresi Hoffmann, 1958 (stat. rev.) is considered as a distinct species, whereas M. alboscutellatus var. atratulus (Solari, 1933) is maintained as a subspecies of M. alboscutellatus (Hustache, 1913). The following new synonymies are proposed: Mecinus barbarus Gyllenhal, 1838 (= M. longiusculus var. subcylindricus Pic, 1896 syn. n.); M. caucasicus (Reitter, 1907) (= Gymnetron caucasicum var. rubricum Reitter, 1907 syn. n.); M. comosus Boheman, 1845 (= M. setosus Kiesenwetter, 1864 syn. n.; = M. hesteticus Vitale, 1906 syn. n.; = M. pici Reitter, 1907 syn. n.; = M. pici var. theresae Reitter, 1907 syn. n.); M. elongatus (H. Brisout de Barneville, 1862) (= G. pyrenaeum H. Brisout de Barneville, 1862 syn. n.); M. haemorrhoidalis (H. Brisout de Barneville, 1862) (= M. fairmairei Tournier, 1873 syn. n.; = G. variabile var. brevipenne Desbrochers des Loges, 1893 syn. n.; = G. variabile var. curtulum Reitter, 1907 syn. n.); M. humeralis Tournier, 1873 (= M. tournieri Fairmaire, 1876 syn. n.; = M. lineicollis Reitter, 1907 syn. n.); M. paratychioides (Hoffmann, 1965) (= G. longirostre Pic, 1921 syn. n.); M. longulus (Desbrochers des Loges, 1893) (= G. nigronotatum Pic, 1906 syn. n.; = G. nigronotatum var. vaulogeri Pic, 1930 syn. n.); M. pipistrellus (Marseul, 1871) (= G. concavirostre Stöcklein, 1950 syn. n.); M. plantaginis (Eppelsheim, 1875) (= G. zherichini Korotyaev, 1994 syn. n.); M. pyraster (Herbst, 1795) (= M. schneideri Kirsch, 1870 syn. n.; = M. hariolus Reitter, 1907 syn. n.; = M. pici var. favarcqui Pic, 1915 syn. n.); M. sanctus (Desbrochers des Loges, 1893) (= G. laterufum Pic, 1900 syn. n.); M. simus (Mulsant & Rey, 1859) (= G. mixtum Mulsant & Godart, 1873 syn. n.); M. tychioides (H. Brisout de Barneville, 1862) (= G. aestivum Hoffmann, 1956 syn. n.); M. vulpes (Lucas, 1849) (= G. hircinum Desbrochers des Loges, 1893 syn. n.). The following lectotypes are designated: Curculio labilis Herbst, 1795; C. pyraster Herbst, 1795; Gymnetron alboscutellatum Hustache, 1913; G. alboscutellatum var. atratulum Solari, 1933; G. biarcuatum Desbrochers des Loges, 1871; G. bicolor Gyllenhal, 1838; G. bonnairei Desbrochers des Loges, 1898; G. caucasicum Reitter, 1907; G. conirostre Desbrochers des Loges, 1875; G. hircinum Desbrochers des Loges, 1893; G. ictericum Gyllenhal, 1838; G. ictericum var. albohirtum Desbrochers des Loges, 1893; G. inermicrum Desbrochers des Loges, 1875; G. laterufum Pic, 1900; G. lebedevi Roubal, 1926; G. logesi Pic, 1900; G. longirostre Pic, 1921; G. longulum Desbrochers des Loges, 1893; G. moricei Pic, 1902; G. nigronotatum Pic, 1906; G. nigronotatum var. vaulogeri Pic, 1930; G. pirazzolii Stierlin, 1867; G. plantaginis Eppelsheim, 1875; G. saladense Pic, 1902; G. sanguinipes Chevrolat, 1859; G. seriatum Jacquet, 1888; G. simum Mulsant & Rey, 1859; G. tychioides H. Brisout de Barneville, 1862; G. variabile Rosenhauer, 1856; G. variabile var. brevipenne Desbrochers des Loges, 1893; G. variabile var. curtulum Reitter, 1907; Mecinus andalusicus Faust, 1890; M. angustulus Desbrochers des Loges, 1893; M. angustulus var. rufipennis Pic, 1915; M. brevithorax Desbrochers des Loges, 1893; M. comosus Boheman, 1845; M. echinatus Desbrochers des Loges, 1893; M. fairmairei Tournier, 1873; M. horridulus Desbrochers des Loges, 1893; M. humeralis Tournier, 1873; M. longiusculus var. subcylindricus Pic, 1896; M. nasutus Tournier, 1873; M. pascuorum Gyllenhal, 1813; M. pici Reitter, 1907; M. pici var. favarcqui Pic, 1915; M. pici var. theresae Reitter, 1907; M. reichei Tournier, 1873; M. schneideri Kirsch, 1870; M. sublineellus Faimaire, 1880; M. tournieri Fairmaire, 1876. On the basis of a phylogenetic analysis the species are arranged in seven monophyletic groups and two complexes of species, the latter assembling species with a high degree of phenetic similarity but lacking synapomorphies. A key to species, diagnoses of species groups, redescriptions, synonymies, notes on type specimens, comparative notes, distribution, bionomics when available, photographs of habitus and drawings of rostra, terminalia and other useful characters for taxonomy are provided.